(untitled) (Italian Journal of Public Health, 2007)
Background: Cities are engines of health development and not merely settings for health promotion. However, political scientists contest the extent of their powers and the scope of their influence. Methodology: Assuming local governance is a locus of decision-making about intermediate determinants of health, then there are three methodological challenges to evaluating its impact: first, accounting for context; second, addressing multiple, interactive interventions; and third identifying mechanisms for change. ‘Realist’ evaluation is more appropriate for this task than traditional paradigms of public health research. Review: Commissioned evaluations of the first three phases (1987-2002) of the WHO European Healthy Cities Network are reviewed against the three methodological challenges. Conclusions: These evaluations are stronger in identifying necessary city structures and processes but weaker, as are the Network cities themselves, in identifying change mechanisms which convert sector interventions into health gains. This lacuna is addressed in Phase IV (2003-2008) of the Network by the themes of healthy urban planning and health impact assessment.